Threats to Mangrove Ecosystems and Their Impact on Coastal Biodiversity: A Study on Mangrove Management in Langsa City - M Taufik Rahmadi; Eni Yuniastuti; Ayu Suciani; Meilinda Suriani Harefa; Andri Yusman Persada; Eling Tuhono (Indonesian Journal of Earth Sciences, 2023)
The coastal area is a complex and interconnected system of diverse ecosystems, with mangrove ecosystems standing out as one of the most productive. However, global mangrove ecosystems, including those in Langsa City, face multiple threats from human activities and natural hazards. This study focuses on examining the various threats impacting the mangrove ecosystem in Langsa City, including tourism and urban development, climate change, regional development, human activities, and sedimentation. Mangrove ecosystems have specific requirements for survival, making these threats particularly concerning. Through field observations and analysis, this study explores the impact of these threats on the mangrove ecosystem's well-being and its correlation with the overall coastal biodiversity. Additionally, the research delves into the management practices implemented by the local government to preserve the mangrove ecosystems. The findings reveal the severity of threats to the mangrove ecosystem's viability and its implications for coastal biodiversity sustainability. The study also sheds light on the local government's mangrove management system, providing valuable insights into current conservation efforts. By understanding the threats faced by the mangrove ecosystem and the management practices in place, this research contributes to the preservation and sustainable use of this vital coastal resource.